Canada Goose Management Series: Habitat Modification (Rutgers Cooperative Extension, NJ Agricultural Experiment Station, 2003)
This fact sheet, which is part of a series that examines goose management options that are currently employed, will present information on habitat modification techniques that may deter geese from visiting a property. The technique itself is defined and the advantages and disadvantages of habitat modification are explored with regards to effort, effectiveness, and cost.